PsycEXTRA Dataset 2011
DOI: 10.1037/e620432012-001
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Social Climate of Prisons

Abstract: Acknowledgement and disclaimerWe would like to acknowledge the contribution of Patrick Doyle to this report (through his review of prison therapeutic communities). We are particularly grateful for the help and support of the prison staff and prisoners who participated in this research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0
9

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(71 citation statements)
references
References 77 publications
(114 reference statements)
2
60
0
9
Order By: Relevance
“…It consists of 17 items (15 items scored, 2 positively worded items not scored) and has been validated in forensic psychiatric and prison settings (see Day et al, 2012;Schalast et al, 2009;Howells et al, 2009 (Hogue, 1993) -This is a 32 item uni-dimensional scale for assessing attitudes towards sexual offenders consisting of items such as sex offenders never change.…”
Section: Methodsmentioning
confidence: 99%
“…It consists of 17 items (15 items scored, 2 positively worded items not scored) and has been validated in forensic psychiatric and prison settings (see Day et al, 2012;Schalast et al, 2009;Howells et al, 2009 (Hogue, 1993) -This is a 32 item uni-dimensional scale for assessing attitudes towards sexual offenders consisting of items such as sex offenders never change.…”
Section: Methodsmentioning
confidence: 99%
“…However, creating an optimal climate within a high security forensic setting can be very challenging due to the complex patient population, involuntary admission within a closed setting and the balance between security needs and treatment goals (Burrows, 1991;Campling, Davies, & Farquharson, 2004;Howells, Krishnan, & Daffern, 2007). Moreover, patients and staff members working within forensic psychiatric settings seem to evaluate ward climate differently (Caplan, 1993;Day, Casey, Vess, & Huisy, 2011;Dickens, Suesse, Snyman, & Picchioni, 2014;Howells et al, 2009;Livingston et al, 2012;Long et al, 2011;Moos, 1975;Rossberg & Friis, 2004;Schalast, Redies, Collins, Stacey, & Howell, 2008;Morrison, Burnard, & Phillips, 1997). For instance, Howells et al (2009) found that patients in a high secure hospital service in the United Kingdom (UK) evaluated cohesion among patients more favorably than staff members.…”
Section: Introductionmentioning
confidence: 99%
“…Within the context of safety as a dimension of social capital, this may be reflective of aspects of social capital resources existent for inmates in custody but lacking in availability for operational or clinical staff. The authors report that “more positive perceptions of the social climate were associated with higher levels of readiness for treatment” (Day et al 2011:4) among the study sample. Higher staff morale and reduced stress among the study sample were found when the social climate was perceived as a more positive environment (Day et al 2011).…”
Section: Discussionmentioning
confidence: 96%
“…An exploration into the social climate of Australian prisons utilised the prison social climate measure, EssenCES, to measure “key aspects of a social climate that are considered relevant to offender rehabilitation” (Day et al 2011:5). Results showed that prisoners felt safer than both clinical and operational staff in the prison environment (Day et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation